Disease severity prediction for nursing home-acquired pneumonia in the emergency department. Issue 12 (11th January 2011) - Man, S Y; Graham, C A; Chan, S S W; Mak, P S K; Yu, A H Y; Cheung, C S K; Cheung, P S Y; Lui, G; Lee, N; Chan, M; Ip, M; Rainer, T H
Abstract : Background: Prediction rules exist for the assessment of community-acquired pneumonia but their use in nursing home-acquired pneumonia (NHAP) remains undefined. The objectives of this study were to compare the prognostic ability for severe NHAP of five prediction rules (PSI, CURB-65, M-ATS, R-ATS, España rule), and to evaluate their usefulness to identify patients with less severe disease in the emergency department for outpatient care. Methods: A prospective observational study of consecutive NHAP patients was conducted at a university teaching hospital emergency department in Hong Kong between January 2004 and June 2005. The primary outcome was severe pneumonia (defined as combined 30-day mortality and/or intensive care unit (ICU) admission). Results: 767 consecutive NHAP patients were included. Mean (SD) age was 83.4 (9.0) years; 350 (45.6%) were male and 644 (84.0%) had coexisting illness. 95 patients died within 30 days (12.4%), five patients were admitted to the ICU (0.7%) and 98 patients had severe pneumonia (12.8%). Sensitivity and specificity of each decision rule ranged from 37.8% to 95.9% and 15.1% to 87.6% respectively. The overall predictive performance of each rule was between 0.627 and 0.712. The negative likelihood ratios of PSI (0.27) and CURB-65 (0.23) were lower than M-ATS (0.71), R-ATS (0.45) and España (0.39). After excluding 204 patients with either poor functional status or those >90 years of age, sensitivities of M-ATS (96.0%) and R-ATS (100%) improved greatly with negative likelihood ratios of <0.1. Conclusion: PSI and CURB-65 are useful for identification of patients with less severe NHAP.